Knowledge and Attitude: Two Fundamental Factors that Determine Patient Compliance in Antibiotic Therapy - Liza Pristianty, - (Walter de Gruyter GmbH, 2020)
Background With the development of infectious diseases, the use of antibiotics is increasing. Amoxicillin is a penicillin class of antibiotics that are widely used today. Compliance with amoxicillin can reduce the risk of microbial resistance. Two fundamental factors that determine patient compliance in antibiotic therapy are the patient's knowledge and attitude towards the antibiotic. In this study, we want to know the effect of knowledge and attitudes of patients on their compliance in using amoxicillin antibiotics.